2005
DOI: 10.1021/jp052227s
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Processes in the Carotenoid Zeaxanthin after Excess Energy Excitation

Abstract: Aiming for better understanding of the large complexity of excited-state processes in carotenoids, we have studied the excitation wavelength dependence of the relaxation dynamics in the carotenoid zeaxanthin. Excitation into the lowest vibrational band of the S2 state at 485 nm, into the 0-3 vibrational band of the S2 state at 400 nm, and into the 2B(u)+ state at 266 nm resulted in different relaxation patterns. While excitation at 485 nm produces the known four-state scheme (S2 --> hot S1 --> S1 --> S0), exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
126
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(147 citation statements)
references
References 54 publications
20
126
1
Order By: Relevance
“…The profiles were normalized at their maxima; f the steady-state absorption spectrum (dotted line) and the TA spectrum taken in NIR range expressed in wavenumber scale and overlaid to obtain the best peak-valley agreement. The shift required to bring the spectra to coincidence defines the S 1 (2 1 A g -) state energy (11,350 cm -1 ) Photosynth Res (2011) 110:49-60 53 spectral shape and lifetime of *0.5 ps suggest that this EADS is associated with the ESA occurring from the vibrationally not equilibrated S 1 (2 1 A g -) state that was observed for a number of Cars with N = 11 and shorter in solvent environment as well as in a protein (Billsten et al 2003(Billsten et al , 2005Larsen et al 2003;Niedzwiedzki et al 2007Niedzwiedzki et al , 2009Papagiannakis et al 2006;Pendon et al 2005;Wohlleben et al 2003Wohlleben et al , 2004. The lifetime of the S 1 (2 1 A g -) state obtained from the fitting is 3.4 ps.…”
Section: Resultsmentioning
confidence: 88%
“…The profiles were normalized at their maxima; f the steady-state absorption spectrum (dotted line) and the TA spectrum taken in NIR range expressed in wavenumber scale and overlaid to obtain the best peak-valley agreement. The shift required to bring the spectra to coincidence defines the S 1 (2 1 A g -) state energy (11,350 cm -1 ) Photosynth Res (2011) 110:49-60 53 spectral shape and lifetime of *0.5 ps suggest that this EADS is associated with the ESA occurring from the vibrationally not equilibrated S 1 (2 1 A g -) state that was observed for a number of Cars with N = 11 and shorter in solvent environment as well as in a protein (Billsten et al 2003(Billsten et al , 2005Larsen et al 2003;Niedzwiedzki et al 2007Niedzwiedzki et al , 2009Papagiannakis et al 2006;Pendon et al 2005;Wohlleben et al 2003Wohlleben et al , 2004. The lifetime of the S 1 (2 1 A g -) state obtained from the fitting is 3.4 ps.…”
Section: Resultsmentioning
confidence: 88%
“…No transfer to Chl b is detected. The result of internal conversion (IC) from the S 2 excited state is the population of a vibrationally unrelaxed -hot S1 state(s)-which can be recognized from the excited state absorption (ESA) [58,59] in the 500-620 nm range. It is worthwhile to note the broad shoulder on the blue side of the ESA peaking around 509 nm, where on the ns-timescale it is possible to detect Cars triplet signal (cyan spectrum).…”
Section: Cars-chls Eetmentioning
confidence: 99%
“…11,12 There have been debates over the intermediate dark state between the S 2 and S 1 state of many carotenoids [10][11][12]28 but it lacks more experimental and theoretical evidences to unveil the exact nature of the S*/hot S 1 state. We also found that the intensity of the S*/hot S 1 absorption band increased 2-3 times when an excess-energy excitation of 405 nm was used instead of a 490 nm excitation.…”
Section: -19mentioning
confidence: 99%
“…Polivka and co-workers showed that the excited state absorption from the intermediate S* state of zeaxanthin increased with increasing excess vibrational energy above the bottom of the S 2 state. 11 Larsen and co-workers found another state (claimed as the S ‡ state) which showed a longer decay time than that of the S 1 state in β-carotene with 400 nm excess energy excitation.…”
mentioning
confidence: 99%